Implementasi Metode Kaifiyatih Sebagai Upaya Meningkatkan Mutu Bacaan Al-Qur’an Anak-Anak (Studi Desa Karang Anyar, Proppo Pamekasan) - Hidayat, Muhammad Syaiful Bahri; Rohman, Moh. Mujibur (Gayaku Publisher, 2025)
Madrasah Diniyah, TPQ, Mosques and Prayer Rooms are educational institutions that provide various kinds of religious lessons, one of which is reading the holy Qur'an properly and correctly. Learning recitation material and makhorijul huruf is material that is not possible to obtain in public schools. The Islamic religious material obtained in public schools is considered by parents to be inadequate, so parents choose to send their children to madrasah diniyah TPQ, mosques and prayer rooms at night, in order to receive this learning. This research uses qualitative methods with field research or empirical research. Meanwhile, the data in this research was obtained by documentary method. The research results show that the role of Al-Quran teaching methods such as kaifiyati aims to complement existing Al-Quran material, apart from that, so that existing Al-Quran learning can produce students who can read the Al-Quran well and correctly.